EDUCATIONAL BLOG AS A MEANS OF PRESCHOOL TEACHERS PROFESSIONAL EDUCATION - Olha H. Naboka; Maryna O. Demchenko (Інформаційні технології і засоби навчання, 2019)
The article is devoted to the actual topic of modern higher education – the professional training of future preschool teachers by means of electronic educational resources, among which the educational blog is gaining popularity. The authors have considered the definition «blog»; the functions the blog performs as well as the definition «educational blog» are given. The most widly used characteristics of educational blogs are defined as: periodicity, authorship, thematic orientation, the presence of multimedia, content features, technical basis, type of device. Besides the authors analyzed preschool teachers’ existing blogs which are posted on the blogspot.com platform. The experience of creating and using foreign educational blogs is considered, in particular, fragments of foreign educational blogs of preschool and primary teachers are presented. The typical mistakes that may occur when creating an educational blog are highlighted (without title, anonymity, great number of pages, too long text, grammatical and syntax mistakes, long page loading, bad design, excess animation, without plan, social networks ignoring). Examples of successfully completed preschool teachers’ blogs are presented. The advantages of using educational blogs in the training of future preschool teachers are considered. There are analyzed the results of questionnaires of students and teachers of preschool establishments (educators, methodologists, heads). The structure and content of the educational blog «Professional training of future educators» are described (pages of the main menu, cross-column pages). It is determined that the use of the educational blog «Professional training of future educators», the creation of students' own blogs, their content and support will help to prepare future preschool teachers for their professional activity (cognitive, communicative, informative, methodical).